(untitled) (American Journal of Technology and Applied Sciences, 2023)
In this article, the innovative technologies of the digital economy in the Republic of Uzbekistan and their characteristics, efficiency in use, including the prospects and analytical indicators of the use of innovative technologies in the banking system, are highlighted, and appropriate proposals and recommendations are formulated for the further improvement of remote services of commercial banks.